Do radiographers collimate? A retrospective analysis of radiographic collimation of common musculoskeletal examinations at an adult trauma centre. Issue 1 (1st November 2022) - Ball, Sally; McKerrow, Megan; Murphy, Andrew
Abstract: Introduction: Collimation of the primary beam is an important factor in radiography to reduce dose and improve image quality. The introduction of larger detector plates in direct digital radiography (DR) allows the exposed area to be calculated by removing cropping applied to the image. The aim of this study was to assess whether the exposed area was larger than a reference standard across five different projections on different body types, with the reference size being the corresponding cassette size used in traditional film/screen or computed radiography (CR). Method: A retrospective clinical audit of five common musculoskeletal radiographic projections (AP knee, AP shoulder, horizontal beam lateral hip, lateral cervical spine and lateral facial bones), of 359 patients was undertaken. The electronic cropping was removed from projections, and the superior–inferior, antero‐posterior and medio‐lateral collimation size was measured, depending on the projection. The two measurements were multiplied to give an exposed field of view area. The three measurements were compared with a reference standard, being the size of the corresponding cassette size used in the department on film/screen or computed radiography. Results: From the five projections, 1071 measurements were analysed. 416 (38.8%) of these measurements were less than or equal to the agreed reference standard. 655 (61.2%) were greater than the agreed reference standard. Conclusion: The study demonstrates that the majority (61.2%) of the measurements taken were above the reference standard. This results in an increase in radiation dose to patients and detrimental impacts on image quality. Abstract : This retrospective study assessed if the exposed field of a radiographic examination was larger than a reference standard across five different projections on different body types, with the reference size being the corresponding cassette size used in traditional computed radiography. This study found that patients are being over‐exposed to radiation due to inadequate collimation of the primary beam. The ability to digitally crop an image results in exposed anatomy not being examined by clinicians. Digital radiography presents a unique opportunity to conduct audits in this area.